Сутність, поняття та ознаки позитивного іміджу органів прокуратури України - Рибалка, Н. О.; Rybalka, N. O. (Вісник Запорізького національного університету. Сер.: Юрид. науки. – 2013. – № 1, ч. 2. – С. 199-204, 2013)
Проаналізовано основні підходи до формування визначення понять «імідж», «імідж органів прокуратури України». Визначено складові елементи іміджу органів прокуратури України. Наголошено, що позитивний імідж органів прокуратури України можна розглянути як сформований у свідомості громадськості образ цих органів, який відображає позитивне ставлення суспільства до діяльності органів прокуратури України, професійності, компетентності та моральності працівників органів прокуратури, які здійснюють правоохоронні функції, а також забезпечують захист прав та законних інтересів громадян.

The basic approaches to the formation of the definitions of «image», «image prosecutor organs of Ukraine» are analyzed. Components of image of prosecutor organs Ukraine are defined. Concept «positive image of prosecutor organs of Ukraine» are formed. The visual image of prosecutor organs of Ukraine consists of aesthetics of clothing (appearance) prosecutors and conditions (equipment rooms, facilities, availability of means) in which they work. Uniforms not only commands respect to persons, with whom the prosecutor communicates, but also to some extent discipline himself, as it is reminder of high calling and responsibility of tasks undertaken by the prosecutor's office. Image of prosecutor organs of Ukraine – an internal and external image of the organs of Ukraine, which manifests itself in public attitudes towards transparency of prosecutor organs of Ukraine, their role in the formation of Ukraine as a legal, democratic and social state, professionalism, competence, activity, morality, ethics, communication, mannerisms, culture workers of a prosecutor organs, as well as the aesthetics of clothing (appearance) and the conditions in which they work. The constituent elements of the image of the prosecutor of Ukraine are: 1) public image, 2) image management and image of the employees of prosecutor organs, 3) a visual image of prosecutor organs. Positive image of prosecutor organs of Ukraine can be defined as formed in the minds of the public image of these organs, which reflects a positive attitude towards the prosecution of Ukraine, professionalism, competence and morality prosecutors who carry out law enforcement functions and protect the rights and legitimate interests of citizens.

Проанализированы основные подходы к формированию определения понятий "имидж", "имидж органов прокуратуры Украины". Определены составные элементы имиджа органов прокуратуры Украины. Отмечено, что позитивный имидж органов прокуратуры Украины можно рассмотреть как сформированный в сознании общественности образ этих органов, отражающий положительное отношение общества к деятельности органов прокуратуры Украины, профессиональности, компетентности и нравственности работников органов прокуратуры, осуществляющих правоохранительные функции, а также обеспечивающих защиту прав и законных интересов людей.
Nature, concept and characteristics of positive image of prosecutor organs of Ukraine
Сущность, понятие и признаки позитивного имиджа органов прокуратуры Украины
Рибалка, Н. О. Сутність, поняття та ознаки позитивного іміджу органів прокуратури України / Рибалка Н. О. // Вісник Запорізького національного університету. Сер.: Юрид. науки. – 2013. – № 1, ч. 2. – С. 199-204.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; прокуратура; органи прокуратури; prosecutor's office; органы прокуратуры; імідж; image; имидж; позитивний імідж; positive image; положительный имидж; громадський імідж; авторитет